A Novel Quinoline Derivative for Selective and Sensitive Visual Detection of PPB Level Cu2+ in an Aqueous Solution - Das, Nilimesh; Khan, Tanmoy; Das, Aritra; Jain, Vipin K.; Acharya, Joydev; Faizi, Md. S. H.; Daniel, Joseph; Sen, Pratik (Current Analytical Chemistry, 2022)
Aim: Selective and sensitive visual detection of Cu2+in aqueous solution at PPB level using an easily synthesized compound. Background: The search for a chemosensor that can detect Cu2+ is very long owing to the fact that an optimum level of Cu2+ is required for human health and the recommended amount of Cu2+ in drinking water is set to be 1-2 mgL-1. Thus, it is very important to detect Cu2+ even at a very low concentration to assess the associated health risks. Objective: We are still seeking the easiest, cheapest, fastest and greenest sensor that can selectively, sensitively and accurately detect Cu2+ with the lowest detection limit. Our objective of this work was to find one such Cu2+ sensor. Methods: We have synthesized a quinoline derivative following very easy synthetic procedures and characterized the compound by standard methods. For the sensing study, we used steady state absorption and emission spectroscopy. Results: Our sensor can detect Cu2+ selectively and sensitively in an aqueous solution instantaneously, even in the presence of an excess amount of other salts. The pale-yellow color of the sensor turns red on the addition of Cu2+. There is no interference from other cations and anions. A 2:1 binding mechanism of the ligand with Cu2+ is proposed using Jobs plot with binding constant in the order of 109 M-2. We calculated the LOD to be 18 ppb, which is quite low than what is permissible in drinking water. Conclusion: We developed a new quinoline based chemosensor following a straightforward synthetic procedure from very cheap starting materials that can detect Cu2+ visually and instantaneously in an aqueous solution with ppb level sensitivity and zero interference from other ions.
Keywords: aqueous solution